Trinidad Chacachacare Lighthouse - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
Photo of a lighhouse located in Chacachacare Trinidad.
Colour: Sepia ; Style: Portrait ; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Lighthouses; Chacachacare Island